Analysis of TikTok Acceptance on Generation Z’s Continuance Intention in Accessing Digital Information Using the UTAUT 3 - Afifa Lutfia Fakhira; Dedy Setiawan (Sisfo: Jurnal Ilmiah Sistem Informasi, 2026)
This study aims to analyze acceptance of TikTok and its effect on continuance intention of Generation Z in obtaining digital information using UTAUT3 model, extended with Trust as an external variable. The increasing use of TikTok as a digital information source among Generation Z raises concerns regarding factors influencing user acceptance and continuance intention, which remain underexplored. This research examines effects of Performance Expectancy, Effort Expectancy, Social Influence, Facilitating Conditions, Hedonic Motivation, Habit, Personal Innovativeness, and Trust on Behavioral Intention and Continuance Intention. A quantitative approach was employed by distributing an online questionnaire to 165 Generation Z TikTok users in Indonesia. The data were analyzed using Structural Equation Modeling (SEM) with Partial Least Squares (PLS) method. Indicate Behavioral Intention significantly affects Continuance Intention. PE, EE, FC, and TR significantly influence BI, while FC, HB, PI, and TR significantly affect CI. In contrast, HB, HM, PI, and SI do not significantly affect BI. The insignificant result of Social Influence indicates social factors may not be the main determinant of Generation Z’s intention, although this aspect has not been explored in depth. This contributes to technology acceptance literature; however, it is limited to Generation Z users in Indonesia and uses a cross-sectional design, which limits generalizability and observation of behavioral changes.